Morphology of the species of Abelia Section Vesalea (Caprifoliaceae) - Villarreal-Quintanilla, José Á.; Estrada-Castillón, A. Eduardo; Villaseñor-Ríos, José L.; de la Rosa-Ibarra, Manuel (Instituto de Ecología, A.C., 2014)
Abelia is a genus of the family Caprifoliaceae distributed in Asia and America. The five known American species are restricted to Mexico and integrate the section Vesalea. The morphology and anatomy between the Mexican species is compared, with reference to Abelia × grandiflora and to some other Asiatic ones. The representatives of section Vesalea are characterized by having strap-like nectariferous glands and obovate seeds.